Labor market integration of new immigrants in Spain - Núria Rodríguez-Planas; Natalia Nollenberger (IZA Journal of Labor Policy, 2016)
Immigrants' employment status has worsened during the Great Recession in Spain. How much of this worsening is due to the recession, and how much to a composition effect? Using Spanish Labor Force Survey data from 2000 through 2011, we compare the employment trajectories of different cohorts of immigrants and natives and find that those who arrived before the 2008 recession had little trouble finding work immediately. In contrast, those who arrived after 2008 struggled to find work as Spanish unemployment rates skyrocketed. In addition, although many immigrants who arrived in Spain between 2000 and 2007 were able to find work and eventually move out of the low-skilled positions, the nature of their jobs did not shield them from the recession. Hence, many became unemployed as the economy shed low- and middle-skilled jobs in sectors dominated by immigrants. Immigrants' individual characteristics, such as gender, country of origin, or educational level, had a limited effect on their employment trajectories. These findings suggest that for many workers, finding middle-skilled work alone isn't enough. Hence, integration policies could aim to help workers transition from the secondary to the primary labor market in order to find their way into more stable employment.
Keywords: J15; J24; J61; J62; 330; Immigrants; Great recession; Spain